Komitmen, Kompetensi dan Kepuasan Kerja Terhadap Kinerja Pegawai PT Bank Mandiri Kantor Cabang Sidrap - Anggerwati, Andi Indah; Syamsuriana, Nur (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This study aims to determine commitment, competence and job satisfaction have a partial effect on the performance of employees of PT. Bank Mandiri (persero) Tbk Sidrap Branch Office. The research method used is quantitative research with multiple linear regression analysis techniques with the influence of commitment, competence and job satisfaction on employee performance. The population in this study were all employees of PT. Bank Mandiri (Persero) Tbk Sidrap Branch Office, totaling 34 people. The sample in this study were all employees, totaling 49 people. The research results show thatcommitment, competence and job satisfaction have a significant effect simultaneously on employee performance at PT. Bank Mandiri Sidrap Branch Office. Commitment and competence have no partial effect on the performance of employees of PT. Bank Mandiri Sidrap Branch Office with a significant value. While the job satisfaction variable partially has a significant effect on employee performance at PT. Bank Mandiri Sidrap Branch Office with a significant value.